Impact of intellectual capital on small-firm growth: a longitudinal study from Inc. 5000. Issue 2 (4th May 2021) - Dimitrov, Stanko; Cozzarin, Brian Paul
ABSTRACT: We explore whether intellectual capital is a precursor to Small and Medium Enterprise (SME) growth. We use data from Inc. 5000 of fast-growing SMEs in the USA and match companies to patent applications. We use a zero-inflated negative binomial model corrected for endogeneity to account for many SMEs without intellectual capital. We find the marginal benefit from intellectual capital on SME growth, revenue, and the number of years on the Inc. 5000 list. Across industries, we find a 1% increase in intellectual capital results in a 3.6% increase in revenue growth. The results change by industry: in particular, IT Services, Software, and Telecommunications are the only sectors that have a positive relationship between intellectual capital and growth. Perhaps surprisingly, SMEs in the Business Services, Engineering, and Health industry sectors experience negative growth with an increase in intellectual capital.